Corporate Volunteering as a Manifestation of Social Responsibilty not Only of Large Enterprises - Kaźmierczak , Magdalena (Studia Oeconomica Posnaniensia, 2016)
Engaging employees in the social initiatives of enterprises, for example, through corporate volunteering, is becoming one of the most popular forms of activities in the area of Corporate Social Responsibility, or CSR. This article presents the concept of corporate volunteering in terms of promoting corporate social responsibility. The author discusses its basic principles and forms, as well as the benefits of voluntary programmes based on the literature and secondary sources relating to employee volunteerism. Furthermore, the author suggests that, in Poland, though the number of employers involved socially is increasing, and corporate volunteering is relatively widespread in promoting its ideas, there is certainly still much to be done, especially in small and medium-sized enterprises.